(untitled) (Journal of Veterinary Medicine and Animal Production, 2023)
This study aimed to evaluate the potentiality of freeze–dried ram testes (FDRT) on growth performance and masculinization of Nile Tilapia (Oreochromis niloticus). A total of 1296 fry (1 day old) were randomly allocated to 27 experimental aquaria. The metabolizable energy concentration (ME) and crude protein percentage (CP) of the diet were 20.08 MJ/Kg and 45%, respectively. The experimental treatments were freeze-dried ram testes (FDRT) at different concentration levels of hormone 30, 60 and 90 ng/ml. Diets were randomly distributed among the experimental treatment aquaria using completely randomized design. The fry fed three times per day at a fixed rate of 20% body weight. Water parameters (temperature, pH, dissolved oxygen, and ammonia) were measured and recorded every week. The result of water parameters was within the recommended range for fish rearing. The total body weight was measured and recorded every week. The fry fed with freeze-dried ram testes 90ng/ml obtained the highest growth rate with mean 0.022 followed by fry fed with 60, 30 ng/ml and control group, with means 0. 020, 0, 019 and 0.016, respectively. There was no significant difference (p> 0.05) among the different treatments. Results revealed that Nile tilapia fry fed with 90ng /ml FDRT gave the highest percentage of a male population with mean 75.55 ± 2,22%, followed by fry fed 60, 30ng/ml FDRT and control group; with means 71.11 ± 5.87, 60.00 ± 3.85and 55±5.87%, respectively.